2010
DOI: 10.1007/s10072-010-0365-7
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in epilepsy (SUDEP): a pilot study on truth telling among Italian epileptologists

Abstract: Sudden unexpected death in epilepsy (SUDEP) is a syndrome where a person with epilepsy dies suddenly and no other cause of death is found. The question of informing patients and their families about SUDEP remains a problematic issue. The aim of this study is to explore whether Italian physicians interested in epilepsy believe that they should discuss SUDEP with patients and/or their families. A total of 315 questionnaire were distributed, of which 195 (61.9%) were returned. Seventeen respondents (8.76%) discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 17 publications
5
43
5
2
Order By: Relevance
“…Most of our patients (61.8%) noted that being informed would cause permanent anxiety, thereby negatively affecting the quality of life, which corresponds to the previously discussed doctor opinions on the effects of being informed (Beran et al, 2004;Vegni et al, 2011;Suna et al, 2015). However, we know from prospective studies that such anxiety will not continue in the long term Tonberg et al, 2015;Xu et al, 2015;Ramachandran Nair and Jack, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most of our patients (61.8%) noted that being informed would cause permanent anxiety, thereby negatively affecting the quality of life, which corresponds to the previously discussed doctor opinions on the effects of being informed (Beran et al, 2004;Vegni et al, 2011;Suna et al, 2015). However, we know from prospective studies that such anxiety will not continue in the long term Tonberg et al, 2015;Xu et al, 2015;Ramachandran Nair and Jack, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the findings of surveys analysing SUDEPdiscussion practices in the UK (Morton et al, 2006), Italy (Vegni et al, 2011), the USA and Canada , where only a small percentage of respondents (7.5%, 7.7%, and 11.6%, respectively) never discuss SUDEP with their patients, we previously reported that only 21% of Latvian neurologists inform their patients about the risk of SUDEP (Suna et al, 2015). The main reason not to disclose SUDEP is the caregivers' belief that being informed about the syndrome might cause permanent anxiety or might have a negative influence on the quality of life by causing fundamental lifestyle changes in epilepsy patients (Beran et al, 2004;Vegni et al, 2011;Suna et al, 2015).…”
Section: Introductioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Since the publication of the findings of the outpatient study of SUDEP [1], there has been considerable debate regarding when and whom to tell about it [5,[19][20][21][22][23][24][25][26][27]. It remains controversial as to whether all patients should be told and when [19,20,[24][25][26][27][28][29].…”
Section: Application Of Bolam Principlementioning
confidence: 99%
“…It remains controversial as to whether all patients should be told and when [19,20,[24][25][26][27][28][29]. The actual telling about SUDEP may have negative consequences [1,28] causing psychological effects and even provoking non-epileptic seizures [28].…”
Section: Application Of Bolam Principlementioning
confidence: 99%